PENGARUH PRICE EARNING RATIO, RETURN ON EQUITY, DAN DEBT TO EQUITY RATIO TERHADAP HARGA SAHAM SUB SEKTOR PROPERTY DAN REAL ESTATE DI BURSA EFEK INDONESIA - Siti Kholifah (Jurnal Administrasi Bisnis Fisipol Unmul, 2020)
The property sector is one sector that is capable of absorbing large numbers of workers and has a multiplier effect and considerable backward linkage to other economic sectors. The property and real estate sub-sectors are quite interesting to be the object of research because investors in investing in stocks choose companies This study aims to determine the effect of PER (X1), ROE (X2), and DER (X3) variables on stock prices (Y) in property and real estate sub-sector companies. PER (X1), ROE (X2), and DER (X3) are used as independent variables while Stock Price (Y) is the dependent variable. The sampling technique was carried out by means of the purposive sampling method and obtained 16 companies as research samples. Data collection technique is the documentation method. Data were analyzed using multiple linear regression techniques with the help of SPSS version 20 statistical software. The results of this study indicate that the PER, ROE, and DER variables simultaneously have a significant effect on stock prices in property and real estate sub-sector companies on the Indonesia Stock Exchange. Partially only PER and ROE variables have a significant effect, while the DER variable has no significant effect. ROE variable is the variable that most influences the stock price.